BUDIDAYA UDANG GALAH (Macrobrachium rosenbergii (de Man, 1879)) SISTEM AKUAPONIK BERBASIS POLIKULTUR DENGAN IKAN TAMBAKAN (Helostoma temminckii Cuvier, 1829) - Setijaningsih, Lies; Gunadi, Bambang; Supriyono, Eddy (BERITA BIOLOGI, 2019)
This experiment aimed to find out the optimum density combinations of prawn (M. rossenbergii (de Man, 1879) and fish of kissing gouramy (Helostoma temminckii Cuvier, 1829) in the polyculture based aquaponic fish culture system. There are four treatments and three replications applied in the Completely Randomized Design experiment. The treatments were the combination of giant freshwater prawn (U) and kissing gouramy (T) densities for one square meter (m2), namely (A) 30 prawns and 100 gouramy (U30T100); (B) 20 prawns and 50 gouramy (U20T50); (C) 30 prawns and 50 gouramy (U30T50) and (D) 20 prawns and 100 gouramy (U20T100). An equal density of aquatic plant of water spinach Ipomoea reptans Poir was planted in each treatment units. The results from 60 days experiment showed that the highest growth of prawn were achieved in treatment C i.e 9,355 ± 1,096 g and survival rates of 75.02±0.67%. The highest growth of kissing gouramy were achieved at treatment D i.e 13,688 ± 1,382 g and survival rates of 86.66±0.83%. The water spinach was able to reduce ammonia, nitrite and nitrate. The lowest reduction was achieved at treatment A, i.e., amonia 6.54 %, nitrite 1,33% and nitrate 5,90%. While the highest reduction of ammonia is 11.72% found at treatment D, 3,52% for nitrite at treatment C and 11,72% for nitrate at treatment D. The highest reduction of Total N dan Total P by water spinach were found at the treatment C i.e. 32.54% and D i.e. 47.62%. According to the dominance and abundance index of plankton, Chlorophyceae and Cyanophyceae were recognized as the dominant class in all treatments.